1999
DOI: 10.1038/12971
|View full text |Cite|
|
Sign up to set email alerts
|

Mice lacking Smad3 show accelerated wound healing and an impaired local inflammatory response

Abstract: The generation of animals lacking SMAD proteins, which transduce signals from transforming growth factor-beta (TGF-beta), has made it possible to explore the contribution of the SMAD proteins to TGF-beta activity in vivo. Here we report that, in contrast to predictions made on the basis of the ability of exogenous TGF-beta to improve wound healing, Smad3-null (Smad3ex8/ex8) mice paradoxically show accelerated cutaneous wound healing compared with wild-type mice, characterized by an increased rate of re-epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

60
687
7
13

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 838 publications
(767 citation statements)
references
References 32 publications
60
687
7
13
Order By: Relevance
“…This finding is consistent with the report that mice lacking Smad3 showed accelerated re-epithelialization during wound healing. 6 In addition to inducing keratinocyte hyperproliferation, Smad7 overexpression appeared to have a direct effect on keratinocyte migration. First, Smad7 expression was increased in migrating cells in comparison with nonmigrating cells.…”
Section: Smad7 Wounded Skin Demonstrates Reduced Smad Signaling Whichmentioning
confidence: 96%
See 2 more Smart Citations
“…This finding is consistent with the report that mice lacking Smad3 showed accelerated re-epithelialization during wound healing. 6 In addition to inducing keratinocyte hyperproliferation, Smad7 overexpression appeared to have a direct effect on keratinocyte migration. First, Smad7 expression was increased in migrating cells in comparison with nonmigrating cells.…”
Section: Smad7 Wounded Skin Demonstrates Reduced Smad Signaling Whichmentioning
confidence: 96%
“…4 Conversely, mice with Smad3 deletion exhibit accelerated wound healing with reduced inflammation. 6 Reduced inflammation in Smad7 tg wounds could be responsible, at least in part, for reduced angiogenesis and collagen production, as both occurred after the re-duction in inflammation was first observed. Many inflammatory cytokines and chemokines are released by leukocytes, which are angiogenic and fibrogenic, 3,30 could be reduced in Smad7 wounds as a result of reduced leukocyte infiltration.…”
Section: Stromal Effects Of Epithelial-specific Smad7 Overexpression mentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of Smad3 was found to result in an impaired mucosal immunity and the T-cell response to TGF-b was diminished Yang et al, 1999b). Furthermore, mice lacking Smad3 exhibit an accelerated wound healing due to an increased rate of re-epithelialization and reduced local in®ltration of monocytes (Ashcroft et al, 1999). Thus, the Smad3 pathway may play an important role in tissue repair and regulation of keratinocytes and monocyte function.…”
Section: Smad Knock-out Micementioning
confidence: 99%
“…9,10,[16][17][18][19] However, the specific TGFb role in keratinocytes during re-epithelialization is unclear, as genetic ablation of TGFb signaling pathway elements accelerates wound re-epithelialization in some settings. [20][21][22][23][24] We previously showed that integrin av is necessary for keratinocyte proliferation in organotypic skin, and thus we hypothesized that av integrins are essential for wound re-epithelialization. 6 Here, we develop a novel, human organotypic wound re-epithelialization assay and show, both in vivo and in vitro, that av integrin function in keratinocytes is required for keratinocyte proliferation and efficient wound reepithelialization.…”
Section: Introductionmentioning
confidence: 99%